2022
DOI: 10.3390/biom12070963
|View full text |Cite
|
Sign up to set email alerts
|

Culture Media Composition Influences the Antibacterial Effect of Silver, Cupric, and Zinc Ions against Pseudomonas aeruginosa

Abstract: Different metals, such as silver (Ag), copper (Cu), and zinc (Zn), have been broadly investigated as metals and cations used both in medicine and everyday life due to their broad spectrum of antibacterial activity. Although the antibacterial action of those metals and their ions is well known and studied, the main problem remains in the standardization of experimental procedures to determine the antimicrobial activity as bacteriological media composition might significantly influence the outcome. The presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The MIC of allicin, a compound extracted from garlic, was also shown to be media-dependent, resulting from its stability and availability in different media [ 41 ]. Other studies showed that the pH of the growth medium can have a significant effect on antimicrobial activity [ 42 ]; however, the pH of MHB and TSB used in this study is typically around pH 7.3 for both [ 43 ], suggesting that pH was not a factor in this case. Furthermore, Buyck et al (2012) [ 44 ] showed that the MIC of the antibiotic azithromycin against Pseudomonas aeruginosa was much lower in eukaryotic cell culture medium compared to MHB, resulting from decreased expression of the opr M gene as well as increased permeability of the outer membrane.…”
Section: Discussionmentioning
confidence: 82%
“…The MIC of allicin, a compound extracted from garlic, was also shown to be media-dependent, resulting from its stability and availability in different media [ 41 ]. Other studies showed that the pH of the growth medium can have a significant effect on antimicrobial activity [ 42 ]; however, the pH of MHB and TSB used in this study is typically around pH 7.3 for both [ 43 ], suggesting that pH was not a factor in this case. Furthermore, Buyck et al (2012) [ 44 ] showed that the MIC of the antibiotic azithromycin against Pseudomonas aeruginosa was much lower in eukaryotic cell culture medium compared to MHB, resulting from decreased expression of the opr M gene as well as increased permeability of the outer membrane.…”
Section: Discussionmentioning
confidence: 82%
“…On the other hand, Muller Hinton broth is much more complex, having all nutrients necessary for bacterial growth. An experiment on how different metal ions interact with different culture media [58] revealed that, silver ions are quite active in both simple and more complex media, producing precipitates (when in M9 media, Ag + ions precipitate to AgCl). It could be deduced that the more nutritious the medium, the more compounds there are for silver to interact with, thus reducing its antibacterial properties.…”
Section: Broth Dilution Methodsmentioning
confidence: 99%
“…As already mentioned, zinc ions exhibit antimicrobial activity that affects both Gram-positive and Gram-negative species, including Staphylococcus epidermidis , S. aureus , Streptococcus mutans , Pseudomonas aeruginosa and Escherichia coli . Moreover, Zn 2+ ions were reported to reduce Candida albicans biofilm [ 5 , 22 , 23 ]. Zn 2+ -doped HAp also promotes osteoblasts proliferation and viability [ 5 , 17 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%